(untitled) (Journal of Parents and Teachers, 2026)
Siblings are not born with brotherhood; it is built through living together and emotional learning. The family is the main focus of brotherhood, where children learn to develop their identity, sense of belonging and understanding of others. To achieve this, parents should not judge or favour one child over another, in order to avoid rivalry. The experiences that occur on a daily basis in a family help siblings learn to cooperate and respect each other.